Nonsampling error in social surveys - McNabb, David E. (Sage Publication, 2014)
A welcome and much-needed addition to the literature on survey data quality in social research, Nonsampling Error in Social Surveys , by David E. McNabb, examines the most common sources of nonsampling error: frame error; measurement error; response error, nonresponse error, and interviewer error. Offering the only comprehensive and non-technical treatment available, the book focus on controlling error shows readers how to eliminate the opportunity for error to occur, and features revealing examples of past and current efforts to control the incidence and effects of nonsampling error. Most importantly, it gives readers the tools they need to understand, identify, address, and prevent the most prevalent and difficult-to-control types of survey errors.